Addressing illegal practices: intergenerational transfer and creative engagement as a way to compensate boomerang effects - Richter, Isabell; Lim, Voon Ching; Fadzil, Kamal Solhaimi Bin; Riordan, Oliver; Pahl, Sabine; Goh, Hong Ching (Frontiers in Communication, 2023)
Introduction This study investigates the effectiveness of using an educational comic book to facilitate the intergenerational transfer of knowledge and intentions concerning dynamite fishing in Borneo, Malaysia. The aim is to explore how children can influence their parents' understanding of the issue and their willingness to address it within the community. Additionally, the research examines unintended reactions within the participant groups. Methods The study employed a controlled experimental design with two groups: a treatment group exposed to the educational comic book and a control group without this intervention. Participants were families residing in communities where dynamite fishing is still practiced. Data collection included pre- and post-intervention surveys and follow-up measurements to assess short-term and long-term effects on knowledge and intentions. Results The findings revealed a successful intergenerational transfer of knowledge from children to parents, evident both in the short and long term. Furthermore, the intergenerational transfer of intentions demonstrated a two-fold pattern. The intention to discuss the dynamite fishing problem within the community was transferred from children to their parents at the second measurement point, highlighting the time required for the development of new intentions. A boomerang effect was observed for the intention to cease dynamite fishing among individuals reliant on fishing for their livelihood. This rebound effect was solely observed in the control group but was effectively mitigated in the treatment group, where engagement with the comic book influenced positive outcomes. Discussion The study's results underscore the power of intergenerational transfer of knowledge and intentions from younger to older generations, facilitated by educational comic books as a communication tool for addressing environmental issues. Moreover, a boomerang effect seen in the control group highlights the complexity of behavior change in economically motivated practices like dynamite fishing. Engaging interventions, such as educational materials, can play a crucial role in curbing these behaviors. Furthermore, the study emphasizes the necessity of carefully monitoring unintended reactions within participant groups, particularly in research related to sensitive topics.